Deficiency of Dab2 (Disabled Homolog 2) in Myeloid Cells Exacerbates Inflammation in Liver and Atherosclerotic Plaques in LDLR (Low-Density Lipoprotein Receptor)-Null Mice—Brief Report. Issue 5 (May 2018) - Adamson, Samantha E.; Polanowska-Grabowska, Renata; Marqueen, Kathryn; Griffiths, Rachael; Angdisen, Jerry; Breevoort, Sarah R.; Schulman, Ira G.; Leitinger, Norbert
Abstract : Objective—: Inflammatory macrophages promote the development of atherosclerosis. We have identified the adaptor protein Dab2 (disabled homolog 2) as a regulator of phenotypic polarization in macrophages. The absence of Dab2 in myeloid cells promotes an inflammatory phenotype, but the impact of myeloid Dab2 deficiency on atherosclerosis has not been shown. Approach and Results—: To determine the role of myeloid Dab2 in atherosclerosis, Ldlr −/− mice were reconstituted with either Dab2-positive or Dab2-deficient bone marrow and fed a western diet. Consistent with our previous finding that Dab2 inhibits NFκB (nuclear factor κ-light-chain-enhancer of activated B cells) signaling in macrophages, Ldlr −/− mice reconstituted with Dab2-deficient bone marrow had increased systemic inflammation as evidenced by increased serum IL-6 (interleukin-6) levels and increased inflammatory cytokine expression levels in liver. Serum lipid levels were significantly lower in Ldlr −/− mice reconstituted with Dab2-deficient bone marrow, and further examination of livers from these mice revealed drastically increased inflammatory tissue damage and massive infiltration of immune cells. Surprisingly, the atherosclerotic lesion burden in Ldlr −/− mice reconstituted with Dab2-deficient bone marrow was decreased compared with Ldlr −/− mice reconstituted with wild-type bone marrow. Further analysis of aortic root sections revealed increased macrophage content and evidence of increased apoptosis in lesions from Ldlr −/− mice reconstituted with Dab2-deficient bone marrow but no difference in collagen or α-smooth muscle actin content. Conclusions—: Dab2 deficiency in myeloid cells promotes inflammation in livers and atherosclerotic plaques in a mouse model of atherosclerosis. Nevertheless, decreased serum lipids as a result of massive inflammatory liver damage may preclude an appreciable increase in atherosclerotic lesion burden in mice reconstituted with Dab2-deficient bone marrow. Abstract : Supplemental Digital Content is available in the text.